ESTUDO DO POTENCIAL DE ADERÊNCIA À TRAÇÃO EM DIFERENTES BLOCOS DE ALVENARIA COM E SEM USO DO CHAPISCO - Lubeck, André; Marquezan, José Pedro; Mohamad, Gihad; Ottoni, Tobias Pigatto; Rizzatti, Eduardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The adhesion between coating mortar and different kinds of block roughness has been the focus of researchers in Brazil. Because of this, the objective of this research was evaluated the influence of different coating mortar applied under different surface of concrete block and clay block masonry. The materials and the components were characterized according to Brazilian standards and test of fresh and hard mortar were done. With this work is possible to conclude that there was a relation between the surface roughness of concrete and clay blocks and the pullout strength with and without plaster mortar.